التظاهرات السريرية للقرحة العفجية المشخصة بالتنظير - علي درويش-ميلاد امطانيوس- عبد الهادي خليل (Latakia University Journal -Medical Sciences Series, 2023)
التظاهرات السريرية للقرحة العفجية المشخصة بالتنظير